Hydroethanolic extract of the inner stem bark of Cedrela odorata has low toxicity and reduces hyperglycemia induced by an overload of sucrose and glucose. (13th March 2015) - Giordani, Morenna Alana; Collicchio, Thiago Carvalho Mamede; Ascêncio, Sergio Donizeti; de Oliveira Martins, Domingos Tabajara; Balogun, Sikiru Olaitan; Bieski, Isanete Geraldini Costa; da Silva, Leilane Aparecida; Colodel, Edson Moleta; de Souza, Roberto Lopes; de Souza, Damiana Luiza Pereira; de França, Suélem Aparecida; Andrade, Claudia Marlise Balbinotti; et al.
Abstract: Ethnopharmacological relevance: Cedrela odorata L. (Meliaceae) is a native plant of the Amazon region and its inner stem bark is used in the treatment of diabetes in the form of maceration in Brazilian popular medicine. Until now, there is no scientific study on this activity. The present study was aimed at evaluating the anti-hyperglycemic activity, anti-diabetic, toxicity, antioxidant and potential mechanism of action of hydroethanolic extract of the inner stem bark of Cedrela odorata . Material and methods: The inner stem bark extract of Cedrela odorata was prepared by maceration in 70% ethanol for 7 days to obtain hydroethanolic extract of Cedrela odorata (HeECo). The preliminary phytochemical analysis was performed according to procedures described in the literature. Selected secondary metabolites detected were quantified by high performance liquid chromatography (HPLC). Acute toxicity of HeECo was investigated in male and female mice with oral administration of graded doses of HeECo from 10 to 5000 mg/kg. Subchronic oral toxicity study was done by oral administration of HeECo (500 mg/kg) and vehicle for 30 days to both sexes of Wistar rats. Clinical observations and toxicological related parameters were determined. Blood was collected for biochemical and hematological analyses, while histological examinations were performed on selected organs. Anti-hiperglycemic and antidiabetic effects were evaluated in streptozotocin-induced diabetic rats. In acute evaluation, the animals received pretreatment with 250 and 500 mg/kg of HeECo, before carbohydrate overload. For subchronic effect, the antidiabetic activity of HeECo was evaluated using the same doses for 21 days. At the end of the treatments, the levels of triacylglycerols, malondialdehyde, total antioxidant status, superoxide dismutase and glutathione peroxidase activities were evaluated in the plasma. Results: The extract showed low acute toxicity. HeECo exhibited inhibitory activity against α-glucosidase and caused a lowering in the peak levels of blood glucose in animals that received glucose overload by 36.7% and 24.1% in the area under the glucose curve (AUC). When the overload was sucrose, HeECo reduced the blood glucose level by 44.4% without affecting AUC. Treatment with HeECo of the blood glucose of the diabetic animals for 21 days did not lead to improvement in weight gain and regularization of the blood glucose level, but reduced the triacylglycerol and malondialdehyde levels by 36.6% and 48.1%, respectively. The activity of the antioxidant enzymes, superoxide dismutase and glutathione peroxidase were significantly increased when compared to diabetic control rats. HPLC analysis showed the presence of polyphenols, such as gallic acid, (−)- gallocatechin and (+)- catechin, the latter is present in higher quantity. Conclusions: Collectively, these data showed that HeECo could blunt the postprandial glycemic surge in rats; possibly through inhibition of alpha-glucosidase and positive modulation of antioxidant enzymes. Our findings confirmed the anti-hiperglycemic activity of HeECo in STZ- diabetic rats. Cedrela odorata is effective in diminishing glucose levels in vitro and in vivo and in ameliorating oxidative damage that occurs in diabetes and/or due to hyperglycemia in rats. According to our results, the efficacy of Cedrela odorata preparation could be due to the presence of active principles with different mode of actions at the molecular level, including α-glycosidases and glucose transporter inhibitors and antioxidant property. Graphical abstract: